The Influence of Celebrity Endorsement, Product Quality, To Buying Decission with Brand Image as Intervention Variables - Ishak genius oberio; Agus Dwi Cahya; Henny Welsa (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to examine the relationship between celebrity endorsement, product quality, and purchasing decisions using brand image as an intervention variable. The research focus is on the user of Garnier products in Yogyakarta. Researchers want to know how celebrity endorsements and product quality affect sales and how brand image can mediate the relationship between the two independent variables. The research method employed quantitative analysis with data collection via an online survey of Garnier product users in Yogyakarta.. The data was analyzed using a two-track regression technique to identify the relationship between independent variables (celebrity endorsement, product quality) and intervening variables (brand image), followed by dependent variables. The findings of this study show that the variable Celebrity endorsment has a significant impact on brand image and purchase intent, while the variable Brand image can mediate the impact of Variable Celebrity endorsment on purchase intent, and Variable Brand image can mediate the impact of Variable Quality.